Effect of different exercise regimens on LVEF and restenosis incidence in patients after PCI: a network meta-analysis and an overview of systematic reviews - Li, Hongpeng; Lu, Li; Han, Zhongyu; Liu, Zhixiang; Pan, Juanhong; Wang, Yongsheng; Gao, Xiuhua; Cai, Yijin; Zhao, Tianyu; Nie, Qian; Zhang, Hongcai; Zhang, Di; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objective: To evaluate the effects of different exercise rehabilitation (ER) programs on LVEF and the incidence of restenosis in patients after percutaneous coronary intervention (PCI) through a systematic review and an integrated network meta-analysis (NMA) to provide a reference for the clinical formulation of ER programs for PCI patients.Methods: Meta-analyses of the effects of different types of ER programs on LVEF and the incidence of reinfarction in post-PCI patients were retrieved from 11 domestic and foreign databases. The methodological and reporting quality of the included systematic reviews were evaluated using the AMSTAR 2 and PRISMA statements. The GRADE scoring system was used to evaluate the quality of evidence found in the studies included in the meta-analysis, and studies with high and intermediate-quality evidence were qualitatively analyzed. Stata software (version 16.0) was used to conduct an integrated NMA of the original RCTs with moderate and low risk of bias.Result: Sixteen meta-analyses were included in this evaluation. The reporting quality of the included meta-analyses was relatively complete, and the methodological quality was low.Seventy RCTs were included in the NMA. The results showed that all types of rehabilitative exercises were safe and effectively increased the LVEF and reduced the incidence of coronary restenosis in patients. The comprehensive exercise program was the most likely to improve LVEF, and the comprehensive exercise program, early exercise program, and high-intensity interval exercise were better than aerobic exercise. Comprehensive exercise programs, early exercise programs, and aerobic exercise reduced the incidence of restenosis in patients.However, Chinese Qigong did not reduce the incidence of restenosis in patients, and there was a risk of bias and inconsistency in the quantitative analysis of restenosis incidence.Comprehensive exercise programs have the greatest therapeutic significance in improving cardiac output and reducing restenosis rates in post-PCI patients. The early exercise program has great potential but requires kinesiologists to work with physicians to structure the program and strengthen out-of-hospital management. Aerobic exercise has the least therapeutic significance, and Chinese Qigong is suitable for promotion based on its better efficacy than aerobic exercise and may be an alternative to aerobic exercise, but more experimental evidence is needed.